Antibiotic resistance in viridans streptococci - Potgieter, Elsa (My University, 1994)
Viridans streptococci are aetiological agents of endocarditis, bacteraemia, dental caries and abscesses of the liver, brain and joints. Viridans streptococci had until recently generally been considered to be uniformly susceptible to antimicrobial agents active against Gram-positive cocci. The susceptibility of 211 viridans streptococci isolated from blood in South Africa between 1988-1991 to eight antimicrobial agents was determined. Thirty-eight percent of the isolates were found to be resistant to penicillin (MICs >0.25 /Mg/ml). Five Streptococcus mitis isolates exhibited increased (MIC 64 and 128 ^g/ml) or high-level (MIC >500 /Mg/ml) resistance to gentamicin. In vitro synergy between penicillin and gentamicin was not demonstrated with these isolates.
A thesis submitted to the Faculty of Medicine, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements of Doctor of Philosophy. Johannesburg 1994
Keywords: Drug Resistance, Microbial; Viridans Streptococci; Endocarditis; Bacteremia; Gram-Positive Cocci